EFEKTIVITAS MYOFASCIAL RELEASE DAN STRENGTHENING EXERCISE TERHADAP NYERI DAN PENINGKATAN AKTIVITAS FUNGSIONAL PADA KONDISI TENSION HEADACHE - Ardiani, Nita; Widodo, Agus; Rahman, Farid (Jurnal Fisioterapi dan Rehabilitasi; Vol 2 No 2 (2018): Jurnal Fisioterapi dan RehabilitasiDO - 10.33660/jfrwhs.v2i2.17, 2018)
Background:The impact of high-end student load on final project would trigger physical stress that such as tension headache. This was influenced by ergonomic position and neck muscle work at low level consentric. The purpose of this research is knowing effect of myofascial release and strengthening exercise to decrease pain and improve functional activity for tension headache condition. Methods: This study was quasy experiment two group with control, conducted on January 6 – Februari 3 2018. Sampling method by incidental sampling approach 16 students were conducted for this study, divided into 2 groups. The treatment group was (myofascial release and strengthening exercise) and performed pain and functional measurements by using VAS (Visual Analogue Scale). data analysis used shapiro wilk test, leuvene test, paired sample t-test, and independent sample t-test Result: The influence of myofascial release and strengthening exercise on the decrease of pain with the result p = 0.000, while the increase of functional activity that is p = 0.000 which means the influence of (+) to the increase of functional activity. The existence of different treatment groups (myofascial release and strenthening exercise) and the control group (strecthing) with p = 0.001. Conclusion: There was influence myofascial release and strengthening exercise on the reduction of pain in the condition of tension headache.